IS ALZHEIMER’S DISEASE RISK FACTOR, APOLIPOPROTEIN E POLYMORPHISM, A RISK FACTOR OF TYPE-2 DIABETES MELLITUS? - P, Yun Xin; P, Janisha; N, Serene; M, Tsu Horng; L, Chun Ren (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Individuals with Type-2 Diabetes Mellitus (T2DM) are known to have higher risk of developing Alzheimer’s Disease (AD). One of the most prominent risk factors of AD is Apolipoprotein E (ApoE) polymorphisms. While ε2 allele is known to have suppression effect, ε4-carriers have 5-30-fold increased risk of developing AD compared to ε3-carriers. In this study, we have developed an efficient blood-based APOE genotyping method to investigate if APOE polymorphism plays roles in T2DM. METHODOLOGY Whole blood were collected from 409 participants (88 prediabetes, 202 diabetes, 119 healthy) under approved study protocol NMRR-15-980-26563. Four allele-specific primers were designed with intentional mismatches at each single nucleotide polymorphism (SNP) sites at rs429358 and rs7412, and two common primers flanking the non-allelespecific region. Single plex polymerase chain reaction (PCR) was carried out using a panel of 5 primer sets, whole blood 2 µL/reaction and KAPA Biosystem’s Blood PCR Mix. Analysis of APOE genotypes against T2DM status were compared using ANOVA tests and chi-square tests (α=0.05). RESULTS Definitive APOE genotype were obtained for 407 participants (99.5% of total subjects). Genotype of two participants were further confirmed using follow-up samples. As expected, ε3 allele (84.23%) is the most common, followed by ε2 (9.05%) and ε4 (6.72%). Interestingly, ε4 is significantly linked to Malays (10.69%, p-value=0.0035). However, no statistical difference is found in the allele distribution across pre-diabetic, diabetic, and healthy participants (p-value=0.763), suggesting there is no direct association of ApoE genotype and T2DM in our cohort. Further analysis also found no particular links of fasting blood glucose, HbA1c and BMI with ε2-, ε3- and ε4-carriers. CONCLUSION ApoE polymorphism is not directly indicative of T2DM in our cohort. However, given that ε4-carriers have increased risk of developing AD, it is imperative to follow up with T2DM ε4-carriers, especially the Malay ethnic, who has a significant prevalence as ε4-carrier.